Appraisal of Carbon Capture, Storage, and Utilization Through Fruit Crops - Sharma, Sunny; Rana, Vishal Singh; Prasad, Heerendra; Lakra, Johnson; Sharma, Umesh (Frontiers in Environmental Science, 2021)
Global climate change is expected with ever rising human population on the planet earth. The different anthropogenic activities have resulted in increased levels of greenhouse gases(GHSs) in the atmosphere, higher temperatures, aberrant precipitation patterns and several other climate change that would affect all lives on this planet. This review article addresses the adaptation and mitigation of climate change through assessment of carbon capture, storage and utilization by fruit crops. Most recently, there is an increasing attention on the carbon cycles of terrestrial ecosystems because biosphere roughly fixes 7 to12 percent of emissions caused by human activities. Perennial plants like Forests, fruit Orchards and grasslands are efficient sinks agent of atmospheric Carbon, whereas field crops are great source of GHGs due to soil disturbance, emission of methane or nitrous oxide from burning straw, and field management involving direct (fuel) or indirect (chemicals) emissions from fossil fuels. Thus, there is a need to establish a novel agricultural systems which can minimize the emissions of harmful gases and is capable of sequestering carbon within the atmosphere. Fruit orchards and vineyards have great structural characteristics like long life cycle; permanent organs such as trunk, branches, and roots; null soil tillage (preserves soil organic matter), high quality and yield which allows them to accumulate more Carbon. Hence, the fruit plants have significant potential to sequester carbon in atmosphere. However, the efficiency of carbon sequestration by different fruit crops and their management systems may vary due to their growth and development patterns, physiological behaviour, biomass accumulation, and environmental factors.